2020
DOI: 10.1287/mnsc.2018.3273
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Discrimination with Reviews in the Sharing Economy: Evidence from Field Experiments on Airbnb

Abstract: Recent research has found widespread discrimination by hosts against guests of certain races in online marketplaces. In this paper, we explore ways to reduce such discrimination using online reputation systems. We conducted four randomized field experiments among 1,801 hosts on Airbnb by creating fictitious guest accounts and sending accommodation requests to them. We find that requests from guests with African American–sounding names are 19.2 percentage points less likely to be accepted than those with white-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(140 citation statements)
references
References 33 publications
6
132
2
Order By: Relevance
“…Racial discrimination is a serious concern in the rapidly growing SE ( Cheng and Foley, 2018 ). Indeed, a recent study of 1801 Airbnb hosts found that those with African-American-sounding names were 19% less likely to be accepted as guests than those with white-sounding names ( Cui et al., 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Racial discrimination is a serious concern in the rapidly growing SE ( Cheng and Foley, 2018 ). Indeed, a recent study of 1801 Airbnb hosts found that those with African-American-sounding names were 19% less likely to be accepted as guests than those with white-sounding names ( Cui et al., 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reputation systems have been previously equated with the "invisible hand" that rewards good producers while punishing poor ones [24, p. 53]. Indeed, research shows that reputation systems can offset social biases among a large heterogeneous and independent population of users at online marketplaces [1,12]. However, processes of reputation formation can also have unintended consequences that might be socially and individually undesirable [27].…”
Section: The (Unintended) Consequences Of Reputation Systemsmentioning
confidence: 99%
“…These results suggest that even subtle cues to a person's race can influence economic decisions. Subsequent studies have demonstrated that these effects can be caused by various cues that indicate a person's race, such as names (Cui et al, 2020;Edelman et al, 2017;Farajallah et al, 2016;Zussman, 2013) and profile photos (Edelman & Luca, 2014;Jaeger et al, 2019). Moreover, racial disparities have been observed in various peer-to-peer markets, including eBay (Ayres et al, 2015), Uber (Ge et al, 2016), and online markets for used cars (Zussman, 2013).…”
Section: Racial Discrimination In Peer-to-peer Marketsmentioning
confidence: 99%